2008
DOI: 10.1136/ard.2008.096123
|View full text |Cite
|
Sign up to set email alerts
|

An open-label pilot study of infliximab therapy in diffuse cutaneous systemic sclerosis

Abstract: In dcSSc infliximab did not show clear benefit at 26 weeks but was associated with clinical stabilisation and a fall in two laboratory markers of collagen synthesis. The frequency of suspected infusion reactions may warrant additional immunosuppression in any future studies in systemic sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 30 publications
2
63
0
1
Order By: Relevance
“…Present biologics have not provided outstanding results and are therefore not presently in routine use. Classic TNF-alpha blockers seem to improve arthritis in SSc without significantly altering mRSS or causing serious adverse events [107,108]. In vitro results, however, support the theory that they may worsen fibrosis through the promotion of TGF-beta secretion [109].…”
Section: Biologics In Ssc Treatmentmentioning
confidence: 41%
“…Present biologics have not provided outstanding results and are therefore not presently in routine use. Classic TNF-alpha blockers seem to improve arthritis in SSc without significantly altering mRSS or causing serious adverse events [107,108]. In vitro results, however, support the theory that they may worsen fibrosis through the promotion of TGF-beta secretion [109].…”
Section: Biologics In Ssc Treatmentmentioning
confidence: 41%
“…It was stated that anti-TNF therapy proved to be effective in a few patients with earlystage scleroderma [2]. However, a recent open-label pilot study showed that a 26-week treatment schedule with infliximab in scleroderma patients showed no clear benefit [3]. Therefore, we could not understand why a therapy whose efficacy and safety in scleroderma had not been demonstrated was administered to these patients.…”
Section: Dear Editormentioning
confidence: 98%
“…45 An open-label pilot study in 16 systemic sclerosis patients demonstrated improvement in skin scores with reduction in collagen secretion noted from cultured lesional fibroblasts (Table 1). [46][47][48] In contrast, there is evidence to suggest that TNFa is a potentially anti-fibrogenic cytokine and its blockade might consequently promote fibrosis. In some studies, TNFa can exhibit anti-fibrotic properties by reducing the expression of collagen and CTGF in dermal fibroblasts, 49 and via suppression of TGFb signaling through nuclear factor (NF)-kappa (K) B induction of Smad 7 in other cell types.…”
Section: Tumor Necrosis Factor Alpha (Tnf)mentioning
confidence: 99%